Psychoanalysis of Freddie Mercury in Bohemian Rhapsody (2018) Directed By Bryan Singer - Fasikh, Mukhlasul; Agni, Mahesa; Murtadho, Abdul Muhid; Nugraheni, Susari (STIBA IEC JAKARTA, 2025)
This research focuses on analyzing the personality of Freddie Mercury from a Personality Theory perspective. The researchers use Sigmund Freud’s psychoanalytic perspective theory. This research method uses the qualitative to analyse the object of research leads to content analysis. It collects data through film transcripts (words, dialogues, sentences, and scenes) as a unit of analysis. After that the data is interpreted based on the point of view of the writers. The sample studied is Freddie Mercury character from the film entitled Bohemian Rhapsody directed by Bryan Singer. There will be two sources of data retrieved from the research object, sexual orientation and personality elements based on the psychoanalytic approach. For this research, the researchers will use deep qualitative methods collect data and sort it into parts. This study focuses on (1) types of sexual orientation based on Freddie Mercury’s character in the film Bohemian Rhapsody (2) types of personality based on Sigmund Freud’s psychoanalytic theory. The results of research on the main character in the Bohemian Rhapsody film are (1) the sexual orientation of the main character based on this film is a bisexual (2) Freddie Mercury Id personality is more dominantly in the Bohemian Rhapsody movie. Based on this analysis, the implication of this research is to help the reader to be able to find his own abilities in solving existing problems and forbid the very importance of childhood in the development of one's personality